2011
DOI: 10.1128/jvi.00794-11
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis Virus-Based Vaccine Protects Hamsters against Lethal Challenge with Andes Virus

Abstract: Andes virus (ANDV) is a highly pathogenic South American hantavirus that causes hantavirus pulmonary syndrome (HPS).A high case fatality rate, the potential for human-to-human transmission, the capacity to infect via aerosolization, and the absence of effective therapies make it imperative that a safe, fast-acting, and effective ANDV vaccine be developed. We generated and characterized a recombinant vesicular stomatitis virus (VSV) vector expressing the ANDV surface glycoprotein precursor (VSV⌬G/ANDVGPC) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 70 publications
3
97
0
Order By: Relevance
“…The difference in mechanisms of protection between rAd5 and rVSV could be mediated by differences in the type of vaccineinduced immune responses generated by these two vectors. Indeed, previous studies in a hamster model of Andes virus infection have shown that, whereas rAd5 engendered a robust cytotoxic T-cell response and a short-lived antibody response (32), the rVSV vaccine generated a potent neutralizing antibody response (33). Despite these differences, both vectors protected animals from lethal Andes virus challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in mechanisms of protection between rAd5 and rVSV could be mediated by differences in the type of vaccineinduced immune responses generated by these two vectors. Indeed, previous studies in a hamster model of Andes virus infection have shown that, whereas rAd5 engendered a robust cytotoxic T-cell response and a short-lived antibody response (32), the rVSV vaccine generated a potent neutralizing antibody response (33). Despite these differences, both vectors protected animals from lethal Andes virus challenge.…”
Section: Discussionmentioning
confidence: 99%
“…27 , 49 , 50 In addition, a dual VSV-based vector expressing the GPs of viruses from two different virus families was shown to protect against both viruses in an animal model with similar short time to protection and post-exposure efficacy as VSV-EBOV. 18 , 51 Now that the safety, efficacy, and feasibility of the VSV platform have been proven, it is time to finally license this platform, as has been recently done in Russia. In addition, moving VSV-based vaccines for other pathogenic viruses with outbreak potential, such as MARV, LASV, and Nipah virus, forward to clinical trials should be a priority.…”
Section: Resultsmentioning
confidence: 99%
“…Using synthetic biology, it would be possible to produce DNA vaccine plasmids against all of the known pathogenic strains of hantaviruses; however, from a vaccine development perspective, this would be expensive, impractical, and unnecessary. We and others have demonstrated that neutralizing antibodies are sufficient to protect against infection and/or disease (14,15,31,37,38). Thus, the production of cross-neutralizing antibodies is a reasonable predictor that the vaccine will be cross-protective.…”
Section: Discussionmentioning
confidence: 99%
“…When Syrian hamsters are exposed to ANDV, they develop a lethal disease that closely resembles HPS in humans (14,23,(31)(32)(33)(34)(35)(36). Recombinant adenovirus and vesicular stomatitis virus vectors encoding ANDV N or glycoproteins have been shown to protect against lethal HPS in the hamster model (34,37). In an earlier study, we found that the HTNV M gene-based DNA vaccine conferred partial but not statistically significant protection against an i.m.…”
Section: Fig 3 Evaluation Of Protection (Puuv) and Cross-protection (mentioning
confidence: 99%